Offshoring and skill-upgrading in French manufacturing: A Heckscher-Ohlin-Melitz view - Juan Carluccio; Alejandro Cun͂at; Harald Fadinger; Christian Fons-Rosen (University of Mannheim, Department of Economics, 2015)
We present a factor-proportions trade model in which heterogeneous firms can offshore intermediate inputs subject to fixed offshoring costs. In the skill-abundant country, high-productivity firms offshore a larger range of labor-intensive inputs to the labor-abundant countries than low-productivity firms. Differently from the traditional versions of factor- proportions trade theory, Heckscher-Ohlin forces operate at the within-industry level, leading to endogenous variation in skill intensity across firms that is positively correlated with firm productivity. Using French firm-level data for the years 1996 to 2007, we provide empirical support for the factor proportions channel through which offshoring to labor-abundantcountries affects the firm-level skill intensities of French manufacturers
urn:nbn:de:bsz:180-madoc-396584
Keywords: F11; F12; F14; 330; offshoring; heterogeneous firms; firm-level factor intensities; Heckscher-Ohlin